Unraveling the Role of Metals and Organic Acids towards Bacterial Antimicrobial Resistance in the Food Chain - Rebelo, A (2023)
Antimicrobial resistance (AMR) has a significant global impact on human, animal, and environmental health. Misuse and overuse of antibiotics in clinical and animal production settings are the main drivers behind the emergence of antimicrobial resistant bacteria. However, other compounds with antimicrobial activity may also contribute to this global public health problem. The aim of this comprehensive review is to provide detailed insights into the impact of metals and organic acids on the emergence and spread of AMR in the food chain, for which their role is not fully understood. The review examines the widespread use of organic acids in the food industry as feed additives or disinfectants, the crucial role of copper in animal growth and the harmful effects of mercury and arsenic as pollutants in food-producing environments. Additionally, it explores the antimicrobial mechanisms of metals and organic acids, the tolerance mechanisms developed by bacteria, and the interplay between genes responsible for metal tolerance and AMR. The comprehensive and integrated data presented highlights the need to further explore and understand the role of metals and organic acids as drivers of AMR to develop well-defined strategies effectively mitigating the AMR crisis within the food chain context.